Using multiple measures of teaching quality to strengthen teacher preparation - Jarod Kawasaki; Karen Hunter Quartz; Jose Felipe Martinez (Arizona State University, 2020)
We argue that teacher preparation programs considering approaches to assess teaching quality should choose measures that appropriately represent the complexity of teaching, have formative value in supporting teacher candidates develop as highly qualified teachers and consider the context, mission, and people that the program desires to serve. The authors are part of a research team working with an urban teacher residency program housed in a university's teacher education program. The increased focus on clinical experience and mandated accountability that accompany federal grants created a fertile space to experiment with different types of measures and data collection approaches, well beyond what is typical in traditional teacher education programs. In this essay, we discuss the philosophy and considerations that informed the selection of these measures in the program, and the processes that were followed to use this data in ways that consider the complexity of teaching and honor the value of data as a tool for program improvement.